Pengaruh Investasi, Tenaga Kerja Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi di Provinsi Jawa Tengah - Bambang Setijawan; Nurul Anwar; Suharno Suharno (Universitas Batanghari, 2021)
The average economic growth of Central Java Province is still low and it is in the fourth lowest rank of the six provinces in Java. This study aims to analyze the effect of investment, labor and government spending on economic growth in Central Java Province for the period 2014 - 2019. The data analysis technique used is multiple linear regression with a panel data approach. The results show that investment, labor and government spending have a positive and significant effect on economic growth in Central Java Province in 2014 - 2019. The implications of this study are 1) retaining incoming investors by providing services in accordance with the development of their respective needs and providing services. incentives so that investors feel comfortable investing their capital and attracting potential new investors to be willing to open a business in Central Java Province 2) increase employment returns, hold apprenticeship projects for prospective workers, improve workforce welfare, and improve the quality of the workforce so that labor productivity employment will increase 3) increase and maximize the allocation of government expenditure funds for potential sectors.